2015
DOI: 10.1108/rpj-10-2012-0096
|View full text |Cite
|
Sign up to set email alerts
|

Optimisation of process parameters for lattice structures

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 37 publications
3
21
0
Order By: Relevance
“…Abele et al [48] claimed that building orientation has not any meaningful effect on the printability of scaffolds in SLM processes. They also claimed that powder adhesions have not any meaningful effect.…”
Section: Introductionmentioning
confidence: 99%
“…Abele et al [48] claimed that building orientation has not any meaningful effect on the printability of scaffolds in SLM processes. They also claimed that powder adhesions have not any meaningful effect.…”
Section: Introductionmentioning
confidence: 99%
“…This implies that horizontal struts should be avoided unless they can be supported with other struts. The results coincide with findings by Abele et al [131].…”
Section: -Biological Compatibility Of Metallic Scaffolds Fabricated Usupporting
confidence: 93%
“…Yan et al also attributed powder adhesion due to balling phenomenon which give rise to beads being formed mainly on laser melted surfaces perpendicular to the building direction [34]. However, Abele et al concluded that building orientation has no significant effect on the manufacturability of lattice structures by SLM [131], which implies that these powder adhesions have no significant effect on the short term mechanical properties. However, the powder adhesion can act as stress concentrators which facilitate fatigue crack initiations, affecting fatigue strength of the porous structures [132,133].…”
Section: -Manufacturability Of Metallic Scaffolds Using Selective Lasmentioning
confidence: 99%
“…The dependence of the main process parameters on the strut porosity was evaluated, but only for one LP and LS level. Abele et al [ 16 ] dealt with dimensional accuracy of the strut structure. The authors tested a laser strategy for lattice structure production focused on high dimensional accuracy of very thin struts (d = 0.2 mm).…”
Section: Introductionmentioning
confidence: 99%